Pengaruh Locus of Control, Komitmen Profesional, dan Pengalaman Audit terhadap Perilaku Akuntan Publik dalam Situasi Konflik Audit dengan Kesadaran Etis sebagai Variabel Pemoderasi - Irma Lumban Gaol; Yunilma Yunilma (Jurnal Kajian Akuntansi dan Auditing, 2020)
The research purpose to know the effects of locus of control, professional commitment, audit experience and ethical reasoning on the behavior of public accountants in the audit conflict situation. Research respondents consist of auditors at public accountant office in padang, Pekanbaru and medan. The amount of questioner which has spread to the respondence about 120 sheets and questioner which can be analyzed about 87 sheets. Data analysis is done with multiple regression analysis by using SPSS 15.0 program. The results of these reseacrch indicate that the locus of control, professional commitment, audit experience and ethichal reasoning as moderation when tested together or simultaneously not have significant to auditor in an audit conflict situation. The results partially on locus of control, professional commitment, audit experience and ethical reasoning as moderation not having a significant effect on the behavior in conflict situations for 0072, 0550, and 0419.